Indian transmigrants : Malaysian and comparative essays - Jain, Ravindra K. (Three Essays Collective, 2009)
Essays on Tamilian labour diaspora in Malaysia. Given the range, intensity and magnitude of contemporary transnational migrations, it seems entirely appropriate to designate this world on the move as comprising, from our point of view, of Indian transmigrants. The movement and global adaptations of this population are spread beyond single home and host societies to multiple locales both vertically and horizontally. Ravindra Jain s empirical studies in this book radiate from the vicissitudes of migrants from India to Malaysia on to those in the Caribbean and further on to Australia. The spectrum of globalization in our times necessitates comparisons over still larger territories; therefore, while focusing on particular Indian transmigrants, East and West, Jain s perspectival vision encompasses the entire field of modern Indian diaspora. As a pioneering and singularly wide-ranging narrative of the diaspora, based primarily on the author s fieldwork, this book unravels facets of socio-cultural pluralism, hybridization, ethnic movements, politico-economic mobility and global modernity over a vast territory. The rich ethnographic detail is interleaved throughout with acute analysis and interpretation. The methodology adopted here invites comparisons over a still wider terrain and is therefore of immense relevance to all students of globalization, international migration, socio-cultural transformation and political economy in the new millennium, with special reference to the Asia-Pacific region.